Rancang Bangun Sistem Pendataan Posyandu Berbasis Web Dengan Framework Laravel - Saputra, Agata Bima; Mariana, Novita (STMIK Banjarbaru, 2023)
“Posyandu” is a basic health activity organized by the community for the community, assisted by health workers. Currently the application of information technology, especially in data and information processing, has not been carried out at Posyandu Harum Sari Tlogomulyo Semarang, so that the recording of mother and toddler data from Posyandu participants is done manually. This results in too many archives, so that the processing and presentation of Posyandu activity report data takes longer. This study proposes a website-based information system model for Posyandu activity data collection, which can be used to collect data on children and mothers in the form of soft files, input immunization results, and record Posyandu agendas. System development uses the Waterfall method, with a structured modeling concept. Functional features in the form of child data collection, mother data collection, cadre data collection, weighing process data collection, and activity agenda data collection were tested using the Blackbox testing technique. The test results show that all functional features of the application have been fulfilled validly.Keywords: Data Collection System; Integrated Healthcare Center; Website; Laravel framework AbstrakPosyandu merupakan kegiatan kesehatan dasar yang diselenggarakan oleh masyarakat untuk masyarakat, yang dibantu oleh petugas kesehatan. Saat ini penerapan teknologi informasi terutama dalam pengolahan data dan informasi belum dilakukan di Posyandu Harum Sari Tlogomulyo Semarang, sehingga percatatan data ibu dan balita peserta Posyandu dilakukan secara manual. Hal tersebut menghasilkan terlalu banyak arsip, sehingga proses pengolahan dan penyajian data laporan kegiatan posyandu menjadi lebih lama. Penelitian ini mengusulkan model sistem informasi pendataan kegiatan posyandu berbasis website, yang dapat digunakan untuk pendataan anak dan ibu dalam bentuk soft file, menginput hasil imunisasi, serta merekam agenda Posyandu. Pengembangan sistem menggunakan metode Waterfall, dengan konsep pemodelan terstruktur. Fitur-fitur fungsional berupa pendataan anak, pendataan ibu, pendataan kader, pendataan proses penimbangan, serta pendataan agenda kegiatan diuji menggunakan teknik pengujian Blackbox. Hasil uji menunjukkan seluruh fitur fungsional aplikasi telah dipenuhi secara valid.Kata Kunci: Sistem Pendataan; Posyandu; Website; Framework Laravel